Changes in special comfort behaviours of geese between 2–7 weeks of age under intensive conditions - Molnár, Marcell; Molnár, Tamás; Bogenfürst, Ferenc (Acta Agraria Kaposváriensis, 1998)
In order to develop rearing and laying technologies under intensive conditions it has great importance to examine the behaviour of geese. Eating, drinking, resting, preening, playing and social behaviours were picked out from the comfort behaviours in our researche. Comparing our results to those presented in the literature we could state that changes in comfort behaviours of geese in first 7 weeks are similar to those of peking, muscovy and mulard ducks. Differences were found in rates of appearing frequency of the several behaviour forms. Decrease in eating, drinking and playing time, and higher rate of resting time inform us about lower activity of geese than of ducks in first weeks of rearing. Strong correlation between drinking and eating time shows the importance of continuous supply of geese with good quality drinking water and the necessary condition to achieve demanded weight gain. Medium correlation between drinking and playing and between eating and playing can explain higher level of feed and water waste.
Keywords: comfort behaviours; geese; intensive conditions